Effects of metabolite of Gliocladium roseum on egg hatching and juvenile activity of Meloidogyne incognita - Wang, L.F.; Xu, Y.L.; Li, S.X.; Li, C.J.; Xue, A.G.
Root-knot disease caused by root-knot nematode is a serious yield limiting factor for several economically important crops including soybean, vegetables, fruit trees, tea, tobacco, and medicinal plants. Control of nematode is currently mostly limited to application of soil nematicides, which are costly and detrimental to the environment and human health. There is a need for alternative management of the root-knot pathogen. The objective of this research was to assess the biocontrol potential of the G. roseum strain ACM941 against the root-knot nematode. Results from this research showed that the culture filtrate and volatile metabolites of G. roseum reduced nematode egg hatch by 80.4 and 41.4 percent and increased juvenile mortality by 86.6 and 75.8 percent, respectively. G. roseum can be used to control M. incognita.
Keywords: GLIOCLADIUM ROSEUM